2009
DOI: 10.1111/j.1548-1433.2009.01076.x
|View full text |Cite
|
Sign up to set email alerts
|

Current Views of European Anthropologists on Race: Influence of Educational and Ideological Background

Abstract: Significant differences in views on race (once a core anthropological concept) occur between scientists from different countries. In light of the ongoing race debate, we present the concept's current status in Europe. On three occasions in 2002-03, we surveyed European anthropologists' opinions toward the biological race concept. The participants were asked whether they agreed that there are biological races within the species Homo sapiens. A dependence was sought between the type of response and several facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 52 publications
0
17
0
Order By: Relevance
“…They found that, “Respondents educated in Western Europe and middle‐aged persons reject race more frequently than respondents educated in Eastern Europe and those from both younger and older generations” (Kaszycka et al. , 43). In addition, they noted that biological anthropologists were more likely to reject biological notions of race more often than scientists in other fields.…”
Section: Race In the Context Of Social Science And Biomedicinementioning
confidence: 99%
“…They found that, “Respondents educated in Western Europe and middle‐aged persons reject race more frequently than respondents educated in Eastern Europe and those from both younger and older generations” (Kaszycka et al. , 43). In addition, they noted that biological anthropologists were more likely to reject biological notions of race more often than scientists in other fields.…”
Section: Race In the Context Of Social Science And Biomedicinementioning
confidence: 99%
“…Indeed, it has been suggested that in anthropology, education made a significant impact on anthropologists' attitudes toward human variation and race and that educational changes might have played an important role in the recent shift towards nonracial approaches by many anthropologists (Littlefield et al, 1982, Kaszycka andŠtrkalj, 2002;Kaszycka et al, 2009). It was also maintained that it is no overstatement to suggest that many medical graduates are poorly equipped to deal with the topic of human variation and its translation into medical practice and research (Wilkinson et al, 2010).…”
Section: Human Variation and Anatomymentioning
confidence: 99%
“…In the 1950s and 1960s many anthropologists argued that race, in any of its meanings, had no place in the study of human variation, as it obscured more than helped to explain complex patterns of human variation. Recent research indicates that the race concept is now abandoned by a majority of Western anthropologists (Lieberman et al, 2004;Kaszycka et al, 2009). However, elements of typology still percolate into modern research.…”
Section: Introductionmentioning
confidence: 99%
“…To some this may seem anachronistic, to say the least, but much of the same conceptual language and imagery can be detected across other anthropological traditions in Europe and elsewhere (Radu et al 2004). One recent survey, for instance, indicates that in the United States almost 80 percent of anthropologists reject the concept of biological races, but only 25 percent do so in Poland (Kaszycka et al 2009). …”
Section: The Way Forwardmentioning
confidence: 99%